PENGARUH FLEXIBLE WORK ARRANGEMENT DAN WORK LIFE BALANCE SEBAGAI PARADIGMA BARU DI TENGAH PANDEMI COVID-19 - Putri Wulandari; Bachruddin Saleh Luturlean (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research aims to prove the effect of flexible work arrangements on employee performance in the Covid-19 period on employees of THE BMT Dharmasraya IT Elementary Foundation. The methods used in this study are quantitative with descriptive and causalitytypes of research. The population used in this study was an employee in the Human Resources Section at the Dharmasraya BMT Foundation with a sample number of 60 respondents with sampling using Saturated sampling technique. The analytical techniques used are descriptive analysis, and multiple linear regression analysis with the help of spss application version 24 for windows. The results showed that flexible work arrangements had a positive and significant effect on employee performance. By having the advantages all employees can manage work time according to their own wishes.